A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 5 years ago
Does anyone understand the zero product principle for quadric equations?
anonymous
 5 years ago
Does anyone understand the zero product principle for quadric equations?

This Question is Closed

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0\[2m ^{2} + 10m=12\]

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0factorize the eq. then equate both to zero. you will get the two roots

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Well it goes like this First rearrange the eqn as follows: \[2m ^{2} + 10m + 12 = 0\]

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0or the formula for fractions verse the equations without fractions would help. I have the information mixed upthe (x+a)(x+b)=0 is all that is stated

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Now the product of the coefficient of m^2 and the constant terms +12 is 24 We have to find factors p and q of 24 so that pq = 24 and p + q = 10

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Can you give me the value of p and q ??

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0would you happen to know the formulas?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Absolutely correct !!!! Ok If we take p as 6 and q as 4 pq = 6 x 4 = 24 and 6+ 4 = 10 So, now we can rewrite the equation as \[2m ^{2} + 6m + 4m + 24 = 0\]

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0I'm solving it step by step for u

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Sorry, I made a mistake with the last eqn !!! It will be \[2m ^{2} + 6m + 4m + 12 = 0\]

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Now we take out common factors as follows: \[2m(m + 3) +4(m + 3) = 0\]

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Now (m + 3) is common and so we can rewrite as follows: \[(m + 3) (2m + 4) = 0\]

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Now according to the zero product principal, a x b = 0 if either a=0 or b=0 So (m+3)(2m+4) = 0 means that either m+3 = 0 ie. m = 3 or 2m +4 = 0 ie 2m = 4 ie m = 4/2 ie m = 2

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0Hope it is clear now???
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.